Ornament glass with high refractive index and stable chemical performance and preparation method thereof
By adjusting the molar ratio of raw materials in jewelry glass and Ti/Ba, a glass system with high refractive index and stable chemical properties is formed, which solves the problem of corrosion resistance of existing jewelry glass in acid and alkali environments, and realizes the jewelry in jewelry Widely used in the industry.
Patent Information
- Application Number
- CN202411608500.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-11-12
AI Technical Summary
The existing jewelry glass has poor acid and alkali resistance to abrasion performance under the premise of ensuring a high refractive index, which affects its application in the jewelry industry.
By adjusting the mass percentage of raw materials such as SiO2, BaCO3, TiO2, La2O3, ZrO2, ZnO, and controlling the atomic molar ratio of Ti/Ba to 1.40-2.20, a glass system with stable high refractive index chemical properties such as BaTiO3 is formed.
Jewelry glass with high refractive index and stable chemical properties can remain stable in an acid-base environment and is not prone to corrosion. It is suitable for jewelry electroplating treatment.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the field of inorganic glass, in particular to a decorative glass with high refractive index and strong acid and alkali corrosion resistance which can be used for decorative products. Background Art
[0002] With the continuous advancement of science and technology, the jewelry market has developed rapidly, and various artificial jewelry materials have emerged. Jewelry glass is one of the main materials for jewelry. Jewelry glass is required to have optical properties such as high refractive index and dispersion to obtain the gloss required by jewelry such as diamonds and crystals. The refractive index of ordinary high-silicon glass is difficult to meet the optical performance requirements of high refractive index of jewelry, so it is necessary to develop special high-refractive index glass to make artificial jewelry. For example, CN109734303A applied by Chengdu Qicai Jewelry Co., Ltd. is composed of auxiliary materials with BaO content of 30-60%, TiO2 content of 20-55%, SiO2 content of 5-10%, Y2O3 content of 0-1% and 0-10% to obtain high-refractive index glass. However, this system with BaO+TiO2 content greater than 80%, as the molar ratio of TiO2 / BaO increases, although the refractive index increases, the temperature range of glass crystallization also becomes wider, resulting in a significant increase in the difficulty of obtaining stable glass, but unfortunately the document does not provide a process for obtaining stable glass. Moreover, in jewelry production, decorative glass is usually embedded in metal or alloy accessories, and it needs to be electroplated with accessories such as gold, silver, copper, etc. During electroplating, decorative glass and accessories need to be cleaned and activated with 60-98% sulfuric acid, 30-40% hydrochloric acid and 20-30% sodium hydroxide solution, which requires that decorative glass also has good chemical stability and can resist acid and alkali corrosion during electroplating. However, it is well known that SiO2 and alkali metal oxides in glass are not resistant to alkali and specific acid corrosion, and the chemical stability of ordinary high-refractive index decorative glass is difficult to meet this requirement, thus affecting the application of decorative glass in the jewelry industry. Summary of the invention
[0003] The purpose of the present invention is to overcome the problem that the current decorative glass has poor acid and alkali abrasion resistance under the premise of ensuring a high refractive index, and to provide a decorative glass that has both a high refractive index and acid and alkali corrosion resistance and stable chemical properties and a preparation method thereof.
[0004] A decorative glass with high refractive index and stable chemical properties is composed of the following raw material components in percentage by mass: SiO2 11%-15%, BaCO3 36%-45%, TiO2 25%-35%, La2O3 3%-10%, ZrO2 7%-15%, ZnO 0%-3%, and auxiliary materials 0-3%, wherein the atomic molar ratio of Ti / Ba is 1.40-2.20.
[0005] Furthermore, the high refractive index and chemically stable decorative glass is composed of the following raw material components in percentage by mass: SiO2 12%-14%, BaCO3 41%-43%, TiO2 27%-34%, La2O3 3%-7%, ZrO2 9%-14%, ZnO 0%-3%, and auxiliary materials 0-2.5%.
[0006] Furthermore, the high refractive index and chemically stable decorative glass is composed of the following raw material components in percentage by mass: SiO2 14%, BaCO3 37%, TiO2 32%, La2O3 3%, ZrO2 10%, ZnO 2.2%, and auxiliary materials 1.8%.
[0007] In the above scheme, the auxiliary material is any one of Er2O3, Nd2O3 and B2O3 or any two or three thereof.
[0008] The present invention also provides a method for producing a high-refractive-index decorative glass with stable chemical properties using the above-mentioned components as raw materials, comprising the following steps: Step (1), after the raw materials are prepared according to the components, they are added into a mixer and stirred for 3-4 hours until they are uniform, and then added into the feeding area of the continuous melting glass furnace in batches of 60-90 kg each time using a feeder; Step (2), controlling the melting temperature of each area of the continuous melting glass furnace to be between 1320-1390° C., and controlling the depth of the liquid in the furnace of the continuous melting glass furnace to be 20-25 cm, to perform melting, clarification, and homogenization; Step (3), preheating the molding mold to a temperature of 150°C-200°C for casting; Step (4), the temperature of the blank is reduced to a demolding temperature of 550°C-600°C, and after the formed blank is removed from the mold, it is buried in expanded perlite for annealing and cooled to room temperature to obtain a decorative glass material.
[0009] Furthermore, the continuous melting glass furnace comprises five zones, and the temperature of each zone is controlled as follows: 1340±20°C in the feeding zone, 1390±10°C in the material processing zone, 1380±10°C in the clarification zone, 1360±10°C in the homogenization zone, and 1350±5°C in the discharging zone.
[0010] The present invention belongs to a TiO2-BaO-SiO2 high refractive index glass system. SiO2, as a network generator oxide, forms a silicon-oxygen tetrahedral structure grid in the glass, is the main body of the glass skeleton, and makes the glass have good chemical stability. In the system, when the coordination number of TiO2 is 4, it plays the role of a network generator. When the coordination number is greater than or equal to 6, it acts similarly to a network exobody. TiO2 can significantly increase the refractive index and dispersion of the glass and improve the chemical stability of the glass. BaCO3 is a network exobody of the glass structure. A high content will significantly increase the density and refractive index of the glass, but will reduce the chemical stability of the glass. The present invention controls the atomic molar ratio of Ti / Ba to be 1.40-2.20, and adds La2O3, ZrO2, and ZnO, so that part of BaCO3 reacts with part of TiO2 to generate BaTiO3, and the refractive index of BaTiO3 is above 2.1, and adjusts crystallization to promote the formation of glass, so as to form a glass system with high refractive index, stable chemical properties, and acid and alkali corrosion resistance.
[0011] In the present invention, if the SiO2 content is too high, not only will the alkali corrosion resistance be deteriorated, but the high-temperature viscosity of the glass will also be increased, resulting in an excessively high melting temperature. Therefore, the present invention controls its mass percentage to be 11%-15%.
[0012] Too little TiO2 will result in a low refractive index, while too much will make it difficult to melt. Therefore, the present invention controls the mass percentage content to be 25%-35%.
[0013] BaCO3 content is high, which will significantly increase the density and refractive index of glass, but will reduce the chemical stability of glass. Therefore, the present invention controls its mass percentage to be 36%-45%. In addition, the atomic molar ratio of Ti / Ba is controlled to be 1.40-2.20, so as to control the crystallization temperature while obtaining a high refractive index to form a stable TiO2-BaO-SiO2 glass system.
[0014] La2O3 is a network exosome that exists in the network in the form of interstitial ions. Its refractive index is 2.0, and it is the main component for achieving high refractive index of glass. An appropriate amount of La2O3 can enhance the chemical stability of glass and appropriately improve alkali resistance, but too much La2O3 will reduce the refractive index due to reduced glass density and also lead to reduced alkali resistance. Therefore, the present invention controls its mass percentage content to 3%-10%.
[0015] ZrO2 has high refractive index and low dispersion properties, and its refractive index is above 2.2. It is usually used as a network exosome in glass. In ZrSiO4 generated by SiO2 and ZrO2, the silicon-oxygen bond and zirconium-oxygen bond have strong bond energy, strong antioxidant properties, and can resist acid and alkali corrosion and chemical dissolution. Introducing ZrO2 into glass can improve the chemical stability of glass, especially acid and alkali corrosion resistance, but when the content is too high, it will increase the glass melting temperature and crystallization tendency. Therefore, the present invention controls its mass percentage content to 7%-15%.
[0016] As a network intermediate, ZnO can enter the network in the glass in the form of [ZnO4] tetrahedron, or exist as an interstitial ion in the state of [ZnO6]. The introduction of an appropriate amount can improve the chemical stability and refractive index of the glass, and can reduce the high-temperature viscosity and expansion coefficient of the glass, but the tendency of glass crystallization increases when the content is too high. The present invention controls the appropriate amount of BaCO3 to ensure that the [ZnO4] state is dominant, so as to improve the stability of the glass structure and improve the glass forming ability. Therefore, the present invention controls its mass percentage to be 0%-3%.
[0017] The present invention further ensures the formation of a stable glass system by controlling the glass melting furnace to 1320-1390° C. and a reasonable ratio of raw materials.
[0018] The present invention has the following beneficial effects: (1) The refractive index of BaTiO3 formed during the melting of the present invention is above 2.1. La2O3 and ZrO2 have both high refractive index and high chemical stability, and are components that promote the formation of a stable TiO2-BaO-SiO2 glass system. At the same time, a TiO2-BaO-SiO2 high refractive index glass system is also produced during the melting, so that the refractive index of the prepared decorative glass is between 1.9 and 2.15.
[0019] (2) The raw materials such as TiO2, La2O3, ZrO2, ZnO, SiO2 in the present invention not only have strong chemical stability, but also the silicon-oxygen bonds and zirconium-oxygen bonds in ZrSiO4 formed when SiO2 and ZrO2 are melted have strong bond energy, which makes its solubility in strong acid and strong alkali solutions very low, greatly improving the chemical stability of the decorative glass. After being immersed in 80% sulfuric acid for more than 1 hour or in 40% hydrochloric acid for more than 10 minutes, the decorative glass will not become foggy or faded, and will remain as bright as before.
[0020] (3) The present invention uses a uniquely designed continuous melting glass kiln capable of mass production, which can effectively control the melting conditions, greatly improve production capacity, and reduce energy consumption and production costs. DETAILED DESCRIPTION
[0021] In order to make the purpose, technical scheme and beneficial effects of the present invention more specific, the present invention is further described below in conjunction with examples, but it is not intended to limit the present invention.
[0022] Example 1 (Ti / Ba molar ratio 2.14) A high-refractive-index acid- and alkali-resistant decorative glass is prepared by the following steps: raw materials are prepared according to mass percentage of SiO2 15%, BaCO3 37%, TiO2 32%, La2O 33%, ZrO2 10%, ZnO 1.5%, and auxiliary materials 1.5%, and then added to a stirrer for 3.5 hours. After being fully stirred, 85±2 kg is added to the feeding area of a continuous melting glass furnace once every 20 minutes using a feeder; the melting temperature of 5 areas of the furnace is controlled to be 100°C. 340±10℃, material zone 1380±5℃, clarification zone 1370±5℃, homogenization zone 1360±5℃, discharge zone 1340±5℃; the depth of the furnace material pool is controlled to be 22±1cm, and the speed of the agitator in the homogenization zone is controlled well; the preheating temperature of the forming mold is 200℃±20℃, and the demolding temperature is 580℃±10℃. After the forming blank is removed from the mold, it is buried in expanded perlite for annealing and taken out after cooling to room temperature to obtain a decorative glass with high refractive index and strong chemical properties.
[0023] Example 2 (Ti / Ba molar ratio 1.82) A high refractive index acid and alkali resistant decorative glass is prepared by the following steps: raw materials are prepared according to mass percentage of SiO2 12%, BaCO3 38%, TiO2 28%, La2O 37%, ZrO2 10%, ZnO 3%, and auxiliary materials 2%. After preparation, add into a mixer and stir for 3.5 hours. After fully stirring, use a feeder to add 80±2 kg into the feeding area of the continuous melting glass furnace once every 20 minutes; control the melting temperatures of the five zones in the furnace to be 1340±10℃ in the feeding zone, 1370±5℃ in the chemical zone, 1375±5℃ in the clarification zone, 1360±5℃ in the homogenization zone, and 1350±5℃ in the discharge zone; control the depth of the liquid in the furnace pool to be 21±1cm, and control the speed of the stirrer in the homogenization zone; the preheating temperature of the forming mold is 180℃±20℃, and the demolding temperature is 550℃±10℃. After the forming blank is removed from the mold, it is buried in expanded perlite for annealing, and taken out after cooling to room temperature to obtain a decorative glass with high refractive index and strong chemical properties.
[0024] Example 3 (Ti / Ba molar ratio 1.48) A high-refractive-index acid- and alkali-resistant decorative glass is prepared by the following steps: raw materials are prepared according to mass percentage of SiO2 13%, BaCO3 45%, TiO2 27%, La2O 37%, ZrO 26%, and auxiliary materials 2%, and then added into a mixer and stirred for 4 hours. After fully stirring, use a feeder to add 70±2 kg into the feeding area of the continuous melting glass furnace once every 20 minutes; control the melting temperatures of the five zones in the furnace to be 1340±10℃ in the feeding zone, 1375±5℃ in the chemical zone, 1380±5℃ in the clarification zone, 1365±5℃ in the homogenization zone, and 1345±5℃ in the discharge zone; control the depth of the liquid in the furnace pool to be 23±1cm, and control the speed of the stirrer in the homogenization zone; the preheating temperature of the forming mold is 200℃±20℃, and the demolding temperature is 530℃±10℃. After the forming blank is removed from the mold, it is buried in expanded perlite for annealing, and taken out after cooling to room temperature to obtain a decorative glass with high refractive index and strong chemical properties.
[0025] Example 4 (Ti / Ba molar ratio 1.40) A high refractive index acid and alkali resistant decorative glass is prepared by the following steps: raw materials are prepared according to mass percentage of SiO2 14%, BaCO3 44%, TiO2 25%, La2O 36%, ZrO 25%, ZnO 3%, and auxiliary materials 3%. After preparation, add the raw materials into a mixer and stir for 3.5 hours. After fully stirring, use a feeder to add 60±2 kg into the feeding area of the continuous melting glass furnace once every 20 minutes; control the melting temperatures of the five zones in the furnace to be 1340±10℃ in the feeding zone, 1390±5℃ in the chemical zone, 1380±5℃ in the clarification zone, 1370±5℃ in the homogenization zone, and 1360±5℃ in the discharge zone; control the depth of the liquid in the furnace pool to be 24±2cm, and control the speed of the stirrer in the homogenization zone; the preheating temperature of the forming mold is 150℃±20℃, and the demolding temperature is 550℃±10℃. After the forming blank is removed from the mold, it is buried in expanded perlite for annealing, and taken out after cooling to room temperature to obtain a decorative glass with high refractive index and strong chemical properties.
[0026] Comparative Example 1 (using Y2O3 instead of La2O3+ZrO2+ZnO) After the raw materials are prepared according to the mass percentage of SiO215%, BaCO337%, TiO232%, Y2O314.5% and auxiliary materials 1.5%, the production method is the same as Example 1.
[0027] Comparative Example 2 (Low La2O3) The raw materials are SiO215%, BaCO337%, TiO232%, La2O31%, ZrO212%, ZnO1.5% in percentage by mass, and auxiliary materials are 1.5%. The process method is the same as that in Example 1.
[0028] Comparative Example 3 (High SiO2 without ZnO) The raw materials are SiO2 16.5%, BaCO3 37%, TiO2 32%, La2O 33%, ZrO2 10% in percentage by mass, and auxiliary materials are 1.5%. The process method is the same as in Example 1.
[0029] Performance testing: 1. Refractive index test: Test according to GB / T 7962 national standard. The results are shown in Table 1.
[0030] 2. Density test: Test according to GB / T7962 national standard. The results are shown in Table 1.
[0031] 3. Corrosion resistance test: Since the time standard for the acid corrosion resistance of electroplated jewelry is to immerse it in sulfuric acid for more than 1 hour and in hydrochloric acid for more than 10 minutes, and the jewelry glass does not become foggy or fade, the corrosion resistance test method of the present invention is: (1) Take a glass sample, cut it into a 10 mm round diamond shape, grind and polish it, clean it and dry it to form a test specimen.
[0032] (2) The samples were immersed in 80% (wt%) sulfuric acid solution and 40% (wt%) hydrochloric acid solution, respectively. The maximum immersion time for the decorative glass to remain unchanged and not faded after immersion was calculated. The results are shown in Table 1.
[0033] Table 1 Sample performance test results It can be seen from the results in Table 1 that, compared with the comparative example, Examples 1-4 of the present invention have achieved high refractive index and high density while also having significantly improved acid and alkali corrosion resistance, thus solving the problem of high refractive index imitation gemstone jewelry glass being difficult to electroplate. In particular, Examples 1-2 have a better overall effect.
[0034] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. The protection scope of the present invention is defined by the claims. Any modification, equivalent substitution, improvement, etc. made to the present invention by those skilled in the art within the essence and protection scope of the present invention should be included in the protection scope of the present invention.
Claims
1. A high refractive index decorative glass with stable chemical properties, characterized in that The invention is composed of the following raw material components in mass percentage: SiO2 11%-15%, BaCO3 36%-45%, TiO2 25%-35%, La2O3 3%-10%, ZrO2 7%-15%, ZnO 0%-3%, and auxiliary materials 0-3%, wherein the atomic molar ratio of Ti / Ba is 1.40-2.
20.
2. The high refractive index and chemically stable decorative glass according to claim 1, characterized in that The invention is composed of the following raw material components in the following mass percentages: SiO2 12%-14%, BaCO3 41%-43%, TiO2 27%-34%, La2O3 3%-7%, ZrO2 9%-14%, ZnO 0%-3%, and auxiliary materials 0-2.5%.
3. The high refractive index and chemically stable decorative glass according to claim 1, characterized in that It is composed of the following raw material components in mass percentage: SiO2 14%, BaCO3 37%, TiO2 32%, La2O3 3%, ZrO2 10%, ZnO 2.2%, and auxiliary materials 1.8%.
4. The high refractive index and chemically stable decorative glass according to any one of claims 1 to 3, characterized in that: The auxiliary material is any one of Er2O3, Nd2O3 and B2O3 or any two or three thereof.
5. A method for preparing a high-refractive index decorative glass with stable chemical properties using the component composition of claim 1 as a raw material, comprising the following steps: Step (1), after the raw materials are prepared according to the components, they are added into a mixer and stirred for 3-4 hours until they are uniform, and then added into the feeding area of the continuous melting glass furnace in batches of 60-90 kg each time using a feeder; Step (2), controlling the melting temperature of each area of the continuous melting glass furnace to be between 1320°C and 1390°C, and controlling the depth of the liquid in the furnace of the continuous melting glass furnace to be between 20 and 25 cm, and performing melting, clarification and homogenization; Step (3), preheating the molding mold to a temperature of 150°C-200°C for casting; Step (4), the temperature of the blank is reduced to a demolding temperature of 550°C-600°C, and after the formed blank is removed from the mold, it is buried in expanded perlite for annealing and cooled to room temperature to obtain a decorative glass material.
6. The method according to claim 5, characterized in that The continuous melting glass furnace comprises five zones, and the temperature of each zone is controlled as follows: 1340±20°C in the feeding zone, 1390±10°C in the material-forming zone, 1380±10°C in the clarification zone, 1360±10°C in the homogenization zone, and 1350±5°C in the discharging zone.
Citation Information
Patent Citations
High-refractive colorless transparent artificial synthetic gem
CN109734303A
Optical glass with high refractive index and manufacturing method thereof
CN102765879A
Ultra-high-refractivity environment-friendly cameo glass and preparation method thereof
CN104445925A
High-refraction-index low-chromatic-dispersion optical glass suitable for precise mold pressing
CN105198207A
Barrier rib forming material, partition wall forming paste and barrier rib forming green sheet
JP2003016927A